2016
DOI: 10.1186/s12889-016-3864-5
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between body mass index and depressive symptoms: the “fat and jolly” hypothesis for the middle-aged and elderly in China

Abstract: BackgroundObesity has been identified as a worldwide epidemic. In China, the highest prevalence of obesity is observed in adults aged ≥45 years old. This study aimed to describe the association between BMI and depressive symptoms among a large representative sample of middle-aged and elderly in China.MethodA longitudinal sample of the middle-aged and elderly (6,224 males and 6,883 females) who were interviewed in the 2011 China Health and Retirement Longitudinal Study was used. A multivariate logistic regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
52
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 56 publications
7
52
1
Order By: Relevance
“…In total, 7119 participants who effectively completed the questionnaires were included in our research. The baseline of demographic variables was shown in Table 1, and most variables based on our previous studies [40][41][42][43][44] Table 1 showed the relationship between various characteristics and BP levels in the participants. Significant differences in distribution were observed between blood pressure status in the men in all of the variables, except cigarette smoking, alcohol consumption, eating habit, social and leisure activities, physical exercise, hepatitis history, anti-diabetic medication, and HDL-C. Age, CRP, HbA1c, FPG, LDL-C, BMI, TG, SUA, SBP, and DBP were significantly higher in hypertension than those in the normotension, whereas, eGFR level were lower in hypertension than that in the normotension.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 7119 participants who effectively completed the questionnaires were included in our research. The baseline of demographic variables was shown in Table 1, and most variables based on our previous studies [40][41][42][43][44] Table 1 showed the relationship between various characteristics and BP levels in the participants. Significant differences in distribution were observed between blood pressure status in the men in all of the variables, except cigarette smoking, alcohol consumption, eating habit, social and leisure activities, physical exercise, hepatitis history, anti-diabetic medication, and HDL-C. Age, CRP, HbA1c, FPG, LDL-C, BMI, TG, SUA, SBP, and DBP were significantly higher in hypertension than those in the normotension, whereas, eGFR level were lower in hypertension than that in the normotension.…”
Section: Resultsmentioning
confidence: 99%
“…Variables like age, educational levels (four categories, illiterate, less than elementary school, high school, and above vocational school), marital status (dichotomous variables, the single and married), place of residence (dichotomous variables, rural and urban), cigarette smoking (three categories, no, former smoke, and current smoke), alcohol consumption (three categories, no, less than once a month, and more than once a month), eating habit (three categories, ≤two meals per day, three meals per day, and ≥ four meals per day), social and leisure activities (dichotomous variables, no and yes), accidental injury (dichotomous variables, no and yes), physical exercise (three categories, no physical exercise, less than physical exercises, and regular physical exercises), history of liver disease (dichotomous variables, no and yes), history of cardiovascular diseases (dichotomous variables, no and yes), antidiabetic medication (dichotomous variables, no and yes), antilipidemic medication (dichotomous variables, no and yes), and antihypertensive medication (dichotomous variables, no and yes) were obtained using a self-reported questionnaire, and most variables based on our previous studies [40][41][42][43][44].…”
Section: Self-reported Factorsmentioning
confidence: 99%
“…Zhou et al [23] found that there was a negative association between BMI and depressive symptoms for males. The study on BMI and depression, including 6224 males and 6883 females, indicated that the underweight subjects were more likely to be depressed compared with the normal weight people, whereas overweight and obese men and women were less likely to be depressed than people of normal weight [24] . In a prospective cohort study of 1024 patients, depression was more common in women with PAD compared to those without PAD [25] .…”
Section: Discussionmentioning
confidence: 98%
“…In addition, cumulative evidences indicate that mental disorder is a common comorbidity of obesity [7,8]. The prevalence of depressive symptoms in children and adolescents was approximate to 14% in China [9], and that in obese children and adolescents even reached to 23.62% [10]. Findings from a 2-year longitudinal study also suggested a significantly increased risk for poor well-being among overweight and obese children [11].…”
Section: Introductionmentioning
confidence: 99%